‘A’ AND ‘V’ PATTERN STRABISMUS - Jaspreet Sukhija; Balwinder Kaur; Zoram Zadeng (Delhi Journal of Ophthalmology)
Introduction Pattern strabismus is vertically inconcomitant strabismus, recognized by change in the degree of horizontal deviation in upgaze and downgaze. This entity has been recognized since long time but much signiicance was not given which resulted in poor surgical outcome in such cases. Due to complex and varied presentation, surgical management of this phenomenon is rather complex.